2016
DOI: 10.1097/iae.0000000000000618
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Photoreceptor Structure Associated With Ellipsoid Zone Disruptions Visualized With Optical Coherence Tomography

Abstract: Purpose To compare images of photoreceptor layer disruptions obtained with optical coherence tomography (OCT) and adaptive optics scanning light ophthalmoscopy (AOSLO) in a variety of pathologic states. Methods Five subjects with photoreceptor ellipsoid zone disruption as per OCT and clinical diagnoses of closed-globe blunt ocular trauma (cg-BOT; n = 2), macular telangiectasia type 2 (MacTel; n = 1), blue cone monochromacy (BCM; n = 1) or cone-rod dystrophy (CRD; n = 1) were included. Images were acquired wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 48 publications
4
55
1
1
Order By: Relevance
“…Using confocal AOSLO, we observed significant disruption of the cone mosaic in areas of an intact EZ, although there was relatively good correspondence between the disruption of the IZ band and disruption of the cone mosaic, consistent with previous results showing that confocal reflectivity corresponds closely to IZ band integrity. 50,65 In addition, we documented remnant cone inner segment structure with split-detector AOSLO beyond the point of EZ termination: in fact, inner segments were observed until the point of ELM collapse. Recent work in patients with macular telangiectasia type 2 has shown that EZ (or IS/OS) layer intensity can spontaneously recover in areas underlying a preserved ELM.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Using confocal AOSLO, we observed significant disruption of the cone mosaic in areas of an intact EZ, although there was relatively good correspondence between the disruption of the IZ band and disruption of the cone mosaic, consistent with previous results showing that confocal reflectivity corresponds closely to IZ band integrity. 50,65 In addition, we documented remnant cone inner segment structure with split-detector AOSLO beyond the point of EZ termination: in fact, inner segments were observed until the point of ELM collapse. Recent work in patients with macular telangiectasia type 2 has shown that EZ (or IS/OS) layer intensity can spontaneously recover in areas underlying a preserved ELM.…”
Section: Discussionmentioning
confidence: 76%
“…En face scans were generated from the horizontal volumes using previously described custom segmentation software. 50 …”
Section: Methodsmentioning
confidence: 99%
“…On AOSLO, photoreceptors appear as bright spots due to their waveguiding properties; light is directed by the inner segment into the outer segment, and then reflected back toward the pupil center [10]. Disruption of the waveguiding properties of photoreceptors on AOSLO has been shown to correspond to disruption of the photoreceptor layers on spectral domain-optical coherence tomography (SD-OCT) [11]. Previous studies using various AO techniques to assess the outer retina in patients with DR have shown decreased perifoveal photoreceptor density [1214], a higher spread in neighbor distances between cones and a deviation from the normal cone packing arrangement [14].…”
Section: Introductionmentioning
confidence: 99%
“…1 Its superior axial resolution makes it valuable in studying individual retinal layers, and implementation of summed volume projections can provide detailed, layer-specific en face images. 25 Despite its use, controversy remains regarding the anatomic origin of the hyperreflective signals corresponding to the photoreceptors and other outer retinal structures on OCT.…”
Section: Introductionmentioning
confidence: 99%